National Corrections Reporting Program, (United States), 2000-2017 ([Verlag nicht ermittelbar], 2020)
The National Corrections Reporting Program (NCRP) compiles offender-level data on admissions and releases from state and federal prisons and post-confinement community supervision. The data are used to monitor the nation's correctional population and address specific policy questions related to recidivism, prisoner reentry, and trends in demographic characteristics of the incarcerated and community supervision populations. The Bureau of Justice Statistics (BJS) has administered the NCRP since 1983. Abt Associates has served as the NCRP data collection agent since October 2010.